Formation of additional structural modules of medical rehabilitation centers for polytrauma in wartime - Krasnozhon, Tetiana (Theory and practice of design, 2022)
This article considers the formation of additional structural modules of medical rehabilitation centers for polytrauma in wartime on the basis of existing institutions of this type, the spatial solution of which is directly influenced by the selected architectural and structural systems. The architecture of medical rehabilitation centers for polytrauma in wartime requires the organization of additional structural modules based on the introduction of new building volumes on the territory of the institution and adaptation of existing functional units to new requirements of the treatment process based on changes in predominant types of lesions that characterized by multiple and combined injuries with a pronounced manifestation of the syndrome of mutual deterioration. The study found that the structure of combat surgical and therapeutic injuries tends to change over time due to the development of weapons and the nature of combat operations, so the architecture of additional structural modules of medical rehabilitation centers of polytrauma requires prior flexibility in architectural and spatial planning of medical and rehabilitation environment that can quickly adapt to the new requirements of wartime medicine. The main stages of the evolution of the formation of medical rehabilitation institutions for participants in hostilities are considered. During the analysis of architectural and constructive systems of health care institutions, in particular medical and rehabilitation centers, the main design requirements for the formation of new building volumes of additional structural modules were identified, as well as the main factors influencing the transformative and adaptive transformation of existing space functional units of the institution. Based on the analysis of architectural and structural systems of institutions of this type, recommendations were given for the formation of additional structural modules of medical rehabilitation centers for polytrauma in wartime on the basis of existing institutions in two areas: organization of individual building volumes and adaptation of existing functional units. Thus, according to the purpose of the study, which is to determine the features of architectural and spatial organization of additional structural modules of medical rehabilitation centers of polytrauma in wartime on the basis of architectural and constructive solutions, the author analyzed the theoretical basis of the study, characterized the specifics of combat surgery and therapeutic trauma which is directly the predominant type of damage during hostilities, identified the main constructive requirements and identified the main factors influencing the architectural and spatial organization of additional structural modules of medical rehabilitation centers of polytrauma.